2022
DOI: 10.3389/fphar.2022.883898
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Fuzi and Ginseng Significantly Increase the Exposure of Aconitines

Abstract: The herb-pair ginseng-Fuzi (the root of Aconitum carmichaelii) is the material basis of Shenfu prescriptions and is popular in traditional Chinese medicine for the treatment of heart failure, and even shock with severe-stage of COVID-19. A narrow therapeutic window of Fuzi may cause significant regional loss of property and life in clinics. Therefore, systemic elucidation of active components is crucial to improve the safety dose window of Shenfu oral prescriptions. A high performance liquid chromatography-mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Ginsenosides can promote the metabolism of the toxic component aconitine, prolong the elimination half-life of active ingredients such as hypaconitine, benzoylmesaconine and songorine, and significantly increase the in vivo exposure of active ingredients. At the same time, some studies have found that ginseng can inhibit the ion disorders, toxicity in calcineurin-nuclear factor of activated T cells (CaN-NFAT3) pathway and inhibition of the cytochrome P450 2J3 (CYP2J3) expression caused by aconitine, and enhance the antioxidant effect of myocardial cells ( Liu et al, 2020 ; Yang et al, 2021 ; Chen Z. Y. et al, 2022 ; Bao et al, 2023 ). Therefore, the compatibility of aconite and ginseng has the effect of ‘reducing toxicity and increasing efficiency’.…”
Section: Sfi -Basic Characteristics and History Of Usementioning
confidence: 99%
“…Ginsenosides can promote the metabolism of the toxic component aconitine, prolong the elimination half-life of active ingredients such as hypaconitine, benzoylmesaconine and songorine, and significantly increase the in vivo exposure of active ingredients. At the same time, some studies have found that ginseng can inhibit the ion disorders, toxicity in calcineurin-nuclear factor of activated T cells (CaN-NFAT3) pathway and inhibition of the cytochrome P450 2J3 (CYP2J3) expression caused by aconitine, and enhance the antioxidant effect of myocardial cells ( Liu et al, 2020 ; Yang et al, 2021 ; Chen Z. Y. et al, 2022 ; Bao et al, 2023 ). Therefore, the compatibility of aconite and ginseng has the effect of ‘reducing toxicity and increasing efficiency’.…”
Section: Sfi -Basic Characteristics and History Of Usementioning
confidence: 99%
“…Fuzi, the lateral roots of Aconitum carmichaelii , is a representative medicine for invigorating Yang and saving lives. It has been widely used as a cardiotonic drug in the clinical applications of traditional Chinese medicine ( Liu et al, 2012 ; Yang et al, 2014 ; Chen et al, 2022 ). As a type of aconitine, mesaconine (MES) is an active compound isolated from Fuzi with a broad spectrum effect on biomedical pharmacology ( Jian et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%